Familial Hypercholesterolemia: Diagnostic Differences between Domestic and Foreign Guidelines - MA Hongyang, YUE Anna, SUN Kangyun (Zhongguo quanke yixue)
Family hypercholesterolemia (FH) is a common genetic metabolic disease, characterized by an abnormal increase in low-density lipoprotein cholesterol (LDL-C), which may manifest as corneal arcus and xanthomas. Long-term high levels of LDL-C can increase the risk of atherosclerotic cardiovascular disease (ASCVD). FH patients have a higher risk of early-onset ASCVD, with homozygous FH being more severe. Global prevalence of FH has gradually gained attention, but diagnosis and treatment still face challenges. Leveraging the release of the 2023 Chinese Lipid Management Guidelines, this article primarily compares domestic and foreign screening and diagnostic approaches to emphasize the importance of screening for lipid profiles and recommend early identification of FH patients. Additionally, genetic testing is also recommended, including not only a few key genes but also other related genes or whole-genome detection. Furthermore, this article compares different guidelines on LDL-C control management levels and ASCVD risk factors for different LDL-C subgroups. It highlights the differences in dietary recommendations, lifestyle advice, and medication control between domestic and foreign guidelines, pointing out that statins are the primary cholesterol-lowering agents universally recognized as important, with combination therapy being particularly crucial. However, for patients who failed to achieve LDL-C control after maximally tolerated therapy, international lipid management guidelines have made updates. Meanwhile, for Homozygous familial hypercholesterolemia (HoFH) patients, high-intensity statin combination therapy with other medications is the preferred approach, and early treatment is crucial; timely consideration of lipoprotein apheresis and Recombinant proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors can help reduce the incidence and mortality rate of ASCVD.